Elementary Graphical Perception for Older Adults: A Comparison with the General Population. (November 2014) - Le, Thai; Aragon, Cecilia; Thompson, Hilaire J; Demiris, George
We identified the graphical perceptual information needs of older adults (≥ 60 years of age) through a set of psychophysical experiments on bar, stacked, and pie charts. The results are compared with those of a general population (< 60 years of age). We conducted the experiments as online remote studies with 202 total participants across two experimental types: (1) comparison judgments of graphs (50 older adults, 50 general population) and (2) proportion judgments of graphs (52 older adults, 50 general population). Older adults took longer than the general population to complete tasks across both comparison (4.09 s) and proportion judgments (3.66 s). However, this translated to an approximately equal level of perceptual accuracy. Bar charts were the most effective graphical display when considering both speed and accuracy. Older adults were more accurate using pie charts compared with the general population in the comparison task.